2015
DOI: 10.1038/srep14971
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes of H2S in smokers and patients of COPD which might involve in inflammation, oxidative stress and steroid sensitivity

Abstract: Oxidative stress and inflammation play crucial role in the pathogenesis of chronic obstructive pulmonary disease (COPD). Most patients with COPD show a poor response to corticosteroids. Hydrogen sulfide (H2S ) has been implicated in the pathogenesis of COPD, but its expression and effects in lung tissue from COPD patients are not clear. In peripheral lung tissue samples from 24 patients, we found that compared with nonsmokers, the protein level of cystathionine-γ-lyase (CSE) was decreased in smokers and COPD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
3
30
0
3
Order By: Relevance
“…Both CSE and CBS were found to be reduced following CS exposure. In agreement to this finding, Sun et al (45) reported lower CSE levels in the lungs of smokers. Since H 2 S in known to reduce blood pressure (53), the lower CSE/ CBS expression in CS mice might contribute to the elevated blood pressure seen in this animal cohort.…”
Section: Discussionsupporting
confidence: 59%
“…Both CSE and CBS were found to be reduced following CS exposure. In agreement to this finding, Sun et al (45) reported lower CSE levels in the lungs of smokers. Since H 2 S in known to reduce blood pressure (53), the lower CSE/ CBS expression in CS mice might contribute to the elevated blood pressure seen in this animal cohort.…”
Section: Discussionsupporting
confidence: 59%
“…Recent study showed that PM was able to induced emphysema and airway inflammation in mice, but the mechanism was not fully understood . In this research, we found that CTH, the main enzyme products H 2 S in lung tissues, was impaired in PMinduced mice emphysema and airway inflammation model, which was consistent with our previous study reported that the protein level of CTH was impaired in smokers and COPD patients (Sun et al, 2015). Moreover, using PPG to inhibit endogenous H 2 S generation aggregated PM-caused lung injury, while the complement of exogenous H 2 S donor NaHS significantly attenuated the PM-induced lung damage.…”
Section: Discussionsupporting
confidence: 92%
“…We previous reported that hydrogen sulfide (H 2 S), a novel gaseous signal molecule, also severed as defense system in lung, was impaired in COPD patients (Chen et al, 2005;Sun et al, 2015). And H 2 S exerted significant protect role in defending against cigarette smoke or ozone exposure caused COPD/ emphysema via the anti-oxidative stress, anti-apoptosis, antiendoplasmic reticulum stress, anti-inflammatory function of H 2 S (Han et al, 2011;Li F. et al, 2016;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Novel H 2 S donors, such as AP39 and RT-O, reduced cigarette smoke-induced ROS levels in vitro in an epithelial ALI culture model and reduced inflammatory cell numbers in the lung and markers of fibrosis in vivo in intranasally smoked mice. Treatment with other antioxidants, such as the mitochondrial-targeted peptide SS-31 and the Nrf2-activating itaconate, showed similar protective effects [71,72,[74][75][76][77]. Thus, mROS scavengers, including mitoQ, SKQ and mitoTempo, may be considered as new potential therapeutics for COPD treatment [70,78].…”
Section: Metabolic Alterations In Lung Ageing and Diseasementioning
confidence: 92%
“…H 2 S is an endogenous mitochondrial specific antioxidant, which is both mitochondrial protective and anti-inflammatory [74]. H 2 S has been reported to be reduced in both human COPD and COPD mouse models [75,76], suggesting that the loss of this antioxidant contributes to disease pathology. Novel H 2 S donors, such as AP39 and RT-O, reduced cigarette smoke-induced ROS levels in vitro in an epithelial ALI culture model and reduced inflammatory cell numbers in the lung and markers of fibrosis in vivo in intranasally smoked mice.…”
Section: Metabolic Alterations In Lung Ageing and Diseasementioning
confidence: 99%